Asset management optimization: Integrated Operations and Maintenance (O&M) Planning - Maria Alexandra Ramalho de Oliveira (2019)
The aim of the dissertation is to study the reliability of distribution energy assets, namely power transformes and distribution lines. On both equipments, different prediction algorithms based on historical records were developed with the intention of predicting future failures of a set of power transformers, and for each individual line. Power transformers' failures estimation serves as an input to build a model which aims to optimize an inventory policy with equipments safety stock.